THE ROLE OF ISLAMIC ORGANIZATIONS IN MOBILIZING VOTERS FOR THE 2024 ELECTION IN MEDAN CITY - Putri Azqia Rahmadani; Junaidi Junaidi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to analyze the role of Islamic organizations in voter mobilization in the 2024 Election in Medan City. Using a case study approach with data collection techniques through interviews, observations, and documentation, this study found that Islamic organizations such as Nahdlatul Ulama (NU) play a strategic role in shaping political awareness and voter preferences. This role is carried out through religious forums and the use of social media, but it is colored by ambiguity between the neutral position of the organization and the practical political affiliation of its cadres. The results show that religion-based voter mobilization can increase political participation, but also harbor the potential for polarization and religious instrumentality. Therefore, it is necessary to strengthen the capacity of Islamic organizations as agents of political education that uphold the values of moderation and inclusivity in democracy.